Poziom i tempo rozwoju morfofunkcjonalnego dzieci w wieku 7–10 lat pochodzących z rodzin malo- i wielodzietnych - Przednowek, Karolina; Przednowek, Krzysztof; Mytskan, Bogdan; Пзедповек, Кароліна; Пзедповек, Кристофор; Мицкан, Богдан (Східноєвропейський національний університет ім. Лесі Українки, 2015)
From the research that the number of children in families in some extent is an important factor with respect to the value of the investigated somatic symptoms, as well as the level of development of physical qualities of children of 7–10 years old, who live in the province of Prykarpatia . It was found that girls and boys which have one or two brothers / sisters are characterized by higher somatic symptoms, in comparison with their peers from large families. It was found that the girls and guys who have one or two brothers / sisters are characterized by higher somatic symptoms, in comparison with their peers from large families. Testing confirmed that the population of boys and girls from small families have the highest level of endurance, reactions (except for the 7- and 10-year-olds) as well as the spatial orientation (only in the group of children with the exception of 10-year-olds). But from large families have found the highest level of power abilities (except for the 7- and 9-year-old girls, and spatial orientation. The dynamics of the rate of development of somatic symptoms and motor abilities (except reaction and spatial orientation) among the population of children regardless of the amount children in the families. Із проведених досліджень очевидно, що кількість дітей у сім’ї деякою мірою є вагомим чинником щодо величини досліджених нами соматичних ознак, а також рівня розвитку фізичних якостей дітей 7–10 років, котрі проживають на території Підкарпатського воєводства. Установлено, що дівчата й хлопці, які мають одного або двох братів/сестер, характеризуються вищими соматичними ознаками, порівняно зі своїми ровесниками з багатодітних сімей. Проведені тестування засвідчили, що популяції хлопців і дівчат із небагатодітних сімей відзначаються вищим рівнем розвитку витривалості, швидкості реакції (за винятком 7- й 10-річних хлопців), а також просторової орієнтації (лише в групі хлопців, за винятком 10-річних). Натомість респонденти з багатодітних сімей виявили вищий рівень силових здібностей (за винятком 7- й 9-річних дівчат), а також просторової орієнтації. Динаміка темпу розвитку соматичних ознак та рухових здібностей (за винятком швидкості реакції й просторової орієнтації) серед популяції хлопців не залежить від кількості дітей у сім’ї.
Рівень і темп морфофункціонального розвитку дітей 7–10 років, які походять із мало- й багатодітних сімей
Keywords: morphological and functional development of children; small and large families of seven; морфофункціональний розвиток; діти; мало- й багатодітні сім’ї